Chemical Composition, Apoptotic Activity, and Antiparasitic Effects of Ferula macrecolea Essential Oil against Echinococcus granulosus Protoscoleces - Mohamed S. Alyousif; Hiba Riyadh Al-Abodi; Hamdan Almohammed; Abdullah D. Alanazi; Hossein Mahmoudvand; Marzieh Hakami Shalamzari; Iraj Salimikia (Molecules, 2021)
Background: Today, the present protoscolicidals used to minimize the serious risks during hydatid cyst surgery are not completely safe and have various adverse side effects. The present study aimed to evaluate the chemical composition and apoptotic activity of Ferula macrecolea essential oil (FMEO) as well as its in vitro and ex vivo protoscolicidal effects against hydatid cyst protoscoleces. Methods: Gas chromatography/mass spectrometry (GC/MS) analysis was performed to determine the chemical composition of FMEO. Protoscoleces of hydatid cysts were collected from liver fertile hydatid cysts of infected sheep and were then treated with various concentrations of the essential oil (75, 150, and 300 µL/mL) for 5–60 min in vitro and ex vivo. Then, by using the eosin exclusion test, the viability of the protoscoleces was studied. The caspase-3-like activity of the FMEO-treated protoscoleces was also evaluated through the colorimetric protease assay Sigma Kit based on the manufacturer’s instructions. Results: According to GC/MS, the main constituents of the essential oil were terpinolene (77.72%), n-nonanal (4.47%), and linalool (4.35%), respectively. In vitro, the maximum protoscolicidal activity of FMEO was observed at the concentrations of 150 and 300 µL/mL, such that 100% of the protoscoleces were killed after 30 and 20 min of exposure, respectively. Based on the obtained findings, the results demonstrate that FMEO required a longer time to kill protoscoleces ex vivo; after 12 min of exposure to FMEO, only 13.4% of the protoscoleces remained alive. After 48 h of the treatment of protoscoleces, FMEO, in a dose-dependent manner and at doses of 75, 150, and 300 µL/mL, induced the activation of the caspase enzyme by 24.3, 35.3, and 48.3%, respectively. Conclusions: Our findings demonstrate the potent protoscolicidal effects of FMEO in vitro and ex vivo; however, further studies are required to assess the safety and the efficiency of FMEO as a promising scolicidal agent in a preclinical model and clinical setting.